THE EFFECT OF LEARNING THROUGH ZOOM APPLICATION ON STUDENT LEARNING OUTCOMES IN CREATIVITY AND ENTREPRENEURSHIP PRODUCTS IN CLASS XII SMK BINA NUSA - Endang Kurnia Sandi; Nadia Rista (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
In general, the purpose of this study is to describe the effect of the Zoom application on the learning outcomes of class XII students of SMK Bina Nusa Bekasi. The subjects of this study were 20 students of class XII. In this study, the method used is a descriptive survey in which a research method that takes a sample from a population and uses a questionnaire as a data collection tool. In this study, data and information were collected from respondents using a questionnaire. In this study, the technique of collecting data used a Questionnaire (Questionnaire) technique with a Likert scale. Data analysis in this study began by making a questionnaire related to the benefits of the Zoom Meeting application. Then, the questionnaire was distributed to the respondents which was made in the form of a link. Next, the researcher collects the answers from the questionnaires that have been filled out by the respondents. Based on the results of research and discussion on data analysis, it can be concluded that learning through zoom application has a positive influence on the learning outcomes of class XII students of SMK Bina Nusa. This can be shown by the results of hypothesis testing which shows that a significance value of 0.067 > 0.05 is obtained, so it can be concluded that the zoom application variable (X) has an effect on the learning outcome variable (Y). Based on the t value, it is known that the calculated t value is 5.910 > t table 2.101 so it can be concluded that the zoom application variable (X) has an effect on the learning outcome variable (Y).